The effectiveness of modular living wall system for heat reduction a case study of an urban transformation center in Pasir Gudang - Abd Ghafar, Azmiah; Said, Ismail; Yeo, Lee Bak (UiTM Press, 2025)
In urban areas, humans' thermal comfort is a crucial concern related to the Sustainable Development Goals (SDGs). Living wall system (LWS) can be used as a climate mitigation measure to improve temperature at an outdoor building. Studies on LWS' thermal performance of plant species are still scarce, especially for tropical countries. As such, this study aimed to investigate the cooling potential of vegetation with specific plant characteristics. An experimental study of the LWS was undertaken in the industrial city of Pasir Gudang, Malaysia. Four plant species, Philodendron burle-marxii, Phyllanthus cochinchinensis, Nephrolepis exaltata and Cordyline fructicosa 'Miniature', were evaluated in 4-metre (width) x 1-metre (height) of LWS. The study was carried out continuously for three months, from January until March 2019. The data were then analyzed using IBM SPSS Statistic 24. The findings revealed that Philodendron burle-marxii demonstrated the best cooling capacity among the tested plants as it caused its surrounding temperature to be 2.85 oC during the daytime. It was shown that the broader leaves and higher leaf area index value of the species gave a good response to air temperature reduction in the outdoor environment. Meanwhile, Phyllanthus cochinchinensis was the most efficient species as it obtained the highest reduction of surface temperature with an average of 6.17 oC. This study also confirmed that dense branching and multi-stemmed plants influence the lowering of surface temperature with a smaller leaf and higher leaf area index value. In brief, the combination of a higher leaf area index with several plant morphology is recommended for temperature reduction through the different abilities of plant species.